Social Tourism: An Alternative Tourism in Nepal (The Gaze: Journal of Tourism and Hospitality, 2016)
Tourism, an expanding worldwide phenomenon is one of the largest industries and all countries are keenly interested in promoting tourism, although with different objectives. Social tourism is one of  the  least unexplored area in Nepal, if implemented promptly, would contribute significantly in economy and employment. The government should have social tourism policy so that it can be implemented and the activities of tourists and host organizations can be monitored. The policy should outline the role and responsibility, accountability, criteria and minimum standard of tourists and host organizations, and visa policy for the social tourists.The Gaze: Journal of Tourism and Hospitality Vol.6 2014 pp.98-118